Clostridioides difficile infection: a changing treatment paradigm - Yousif Al Naser; Marriam AlGashami; Layth Aljashaami (Gastroenterology Review)
Clostridioides difficile infection (CDI) poses a persistent challenge in healthcare, with substantial morbidity and mortality implications. This comprehensive review explores current CDI management, emphasising guidelines from IDSA, SHEA, and ESCMID. Additionally, this study spotlights recent drug developments that have the potential to reshape CDI treatment paradigms. Within the current treatment landscape, fidaxomicin, vancomycin, bezlotoxumab, and faecal microbiota transplantation offer varied options, each with its unique strengths and limitations. Fidaxomicin, effective yet resource-constrained, presents a dilemma, with vancomycin emerging as a pragmatic alternative. Bezlotoxumab, though augmenting antibiotics, grapples with cost and safety concerns. Meanwhile, faecal microbiota transplantation, highly efficacious, confronts evolving safety considerations. The horizon of CDI treatment also features promising therapies such as SER-109 and Rebyota, epitomising the evolving paradigm. As CDI management advances, the critical role of standardised microbiome restoration therapies becomes evident, ensuring long-term safety and diversifying treatment strategies.